THE PRESENTATION OF POLITENESS STRATEGIES IN THE NOVEL "BAPAKU ARAB, IBUKU CINA, AKU...) SEBUAH NOVEL UNTUK BERCERMIN" BY DINA ALMANSYUR - Novitiara Wulan N. Prasetya, - (2009)
This study entitled The Representation of Politeness Strategies In The Novel "Bapakku Arab, Ibuku Cina, Aku...(Sebuah Novel Untuk Bercermin)" By Dina F. Al Masyur is an attempt to reveal the politeness strategy related to both positive and negative faces. Mainly, this study consists of three research questions, derived from a major question of how the main character uses the politeness strategies in avoiding conflict. The first is to discover the politeness strategies used by the main character. The second is to reveal the most commonly used strategy of politeness by the main character. The last is to explore the social implications of the strategies to positive and negative faces. Mainly, the study is using qualitative method in order to search the answers to the research questions. This study has found out that there are four strategies of politeness applied by the main character, namely, positive politeness, negative politeness, off-record politeness, and on-record politeness. Positive politeness is the most commonly used strategy by the main character. This study also reveals the social implications of the strategies to the faces. It is found that positive politeness is redressed to positive face, while negative politeness is redressed to negative politeness. Off-record and on-record politeness do not have a tendency to support any faces. It can be determined according to the context of conversation.